A Study on the Characterization of the Main Characters in Gabor Csupo’s Bridge to Terabithia (2007) Movie - Adrianus Hariman (University of Darussalam Gontor, 2022)
This study aims to describe physical appearance, personality, social status, and relationship of main characters. The method is descriptive-qualitative. The researcher employed the method of collecting data, describing, analyzing, and then drawing a conclusion. The unit of data is the intrinsic element of the movie, the characterization of the main characters in Bridge to Terabithia's (2007) movie. The data was collected by the researcher himself. The researcher found that the characters of main characters are; (1) Jesse is a twelve-year-old boy who has straw-colored hair, his arms and legs flew out every which way, lonely, a creative boy, a talented artist, caring, emotional, and cooperative. (2) Meanwhile, Leslie is skinny, 12 years old, has blonde hair, tacky clothing, tomboyish, daring, caring, imaginative, and adventurous. Regarding social status, Leslie is from a rich and educated family and has difficulty socializing with others.